s=pr2+2prh

Rewrite the equation as pr2+2prh=s.

pr2+2prh=s

Subtract pr2 from both sides of the equation.

2prh=s-pr2

Divide each term in 2prh=s-pr2 by 2pr.

2prh2pr=s2pr+-pr22pr

Simplify 2prh2pr.

Cancel the common factor of 2.

Cancel the common factor.

2prh2pr=s2pr+-pr22pr

Rewrite the expression.

prhpr=s2pr+-pr22pr

prhpr=s2pr+-pr22pr

Cancel the common factor of p.

Cancel the common factor.

prhpr=s2pr+-pr22pr

Rewrite the expression.

rhr=s2pr+-pr22pr

rhr=s2pr+-pr22pr

Cancel the common factor of r.

Cancel the common factor.

rhr=s2pr+-pr22pr

Divide h by 1.

h=s2pr+-pr22pr

h=s2pr+-pr22pr

h=s2pr+-pr22pr

Simplify each term.

Cancel the common factor of p.

Cancel the common factor.

h=s2pr+-pr22pr

Rewrite the expression.

h=s2pr+-1r22r

h=s2pr+-1r22r

Cancel the common factor of r2 and r.

Factor r out of -1r2.

h=s2pr+r(-1r)2r

Cancel the common factors.

Factor r out of 2r.

h=s2pr+r(-1r)r⋅2

Cancel the common factor.

h=s2pr+r(-1r)r⋅2

Rewrite the expression.

h=s2pr+-1r2

h=s2pr+-1r2

h=s2pr+-1r2

Move the negative in front of the fraction.

h=s2pr-r2

h=s2pr-r2

h=s2pr-r2

Solve for h s=pr^2+2prh